Globalization and the Developing Countries: Emerging Strategies for Rural Development and Poverty Alleviation - Bigman, David (International Service for National Agricultural Research, 2002)
The globalization process and the internal policy reforms that the developing countries have implemented during the past decade have changed the relative prices of practically all their inputs and outputs. Agricultural producers have therefore been forced to change the structure and methods of their production. The objective of this book is to review the impact of globalization on a number of issues. These include the effects of changes in global trading rules and regulations, the removal of trade barriers and the elimination of many country-specific and commodity-specific trade agreements, on the economies of developing countries in general and their agricultural sectors in particular. The book will be of interest to those in the fields of agricultural and development economics.